Wavelet collocation method and multilevel augmentation method for hammerstein equations - Hideaki Kaneko (2018)
A wavelet collocation method for nonlinear Hammerstein equations is formulated. A sparsity in the Jacobian matrix is obtained which gives rise to a fast algorithm for nonlinear solvers such as the Newton's method and the quasi-Newton method. A fast multilevel augmentation method is developed on a transformed nonlinear equation which gives an additional saving in computational time. © 2012 Society for Industrial and Applied Mathematics.